Taurine reduces hyperactive behavior in SHR rats through upregulating the proportion of CD4+CD25+Foxp3+ regulatory T cells. (May 2019) - Chen, Vincent Chin-Hung; Chiu, Chun-Ching; Weng, Jun-Cheng; Chen, Li-Jeng; Siow, Jing Yi; Hsu, Tsai-Ching; Tzang, Bor-Show
Graphical abstract: Highlights: Taurine reduces systolic blood pressure associated hyperactivity in an ADHD animal model. Taurine reduces ADHD-related immune factors in an ADHD animal model. Lower CD4+CD25+Foxp3+ regulatory T cells proportion is associated with hyperactivity in an ADHD animal model. Taurine increases CD4+CD25+Foxp3+ regulatory T cells in an ADHD animal model. Abstract: Attention deficit hyperactivity disorder (ADHD) is a most common mental illness in both children and adults. Our recent studies revealed that high-dose taurine improves hyperactivity in SHR rats by reducing mALFF signal and striatal dopamine uptake. This study further revealed the association between immune factors and hyperactivity in SHR rats fed with high-dose taurine. A positive correlation was detected between systolic blood pressure (SBP) and horizontal locomotion in SHR rats fed with high-dose taurine. Significantly higher striatal Hsp27 and galectin-3 were detected in SHR rats fed with high-dose taurine. Significantly lower IL-2 and IL-6 were detected in SHR rats fed with high-dose taurine, whereas significantly higher IL-10 was detected. Significantly increased splenic CD4+CD25+Foxp3+ regulatory T cells was detected in SHR rats fed with high-dose taurine with a negative correlation. These findings suggest that high-dose taurine reduce hyperactive behavior in SHR rats probably via multifactorial modulation on immune system.